Climate change and marine top predators - Tore Haug (Frontiers Research Topics, 2016)
Climate change affects all components of marine ecosystems. For endothermic top predators, i.e. seabirds and marine mammals, these impacts are often complex and mediated through trophic relationships. In this Research Topic, leading researchers attempt to identify patterns of change among seabirds and marine mammals, and the mechanisms through which climate change drives these changes.